A novel strategy for thermometry based on the temperature-induced red shift of the charge transfer band edge. Issue 5 (11th January 2018) - Zhou, Shaoshuai; Duan, Changkui; Han, Shuo
Abstract : A novel ratiometric temperature sensing strategy based on the temperature-induced red shift of the CTB is proposed. Abstract : We report a novel strategy for optical temperature sensing using the temperature-induced red shift of the charge transfer band (CTB) edge of the VO4 3− groups in GdVO4 :5% Sm 3+ . Excitation spectra were recorded at a series of temperatures ranging from 300 to 480 K. It is demonstrated that an excitation intensity of around 360 nm corresponding to the tail of the CTB and an excitation intensity of 407.6 nm corresponding to the 6 H5/2 → 4 F7/2 transition of Sm 3+ exhibit opposite temperature dependence. Based on this, the relative sensitivity was obtained to be 3313/ T 2 in our investigated temperature range, which is remarkable progress compared with the optical temperature sensors reported previously. We believe that this work broadens the pathway for the design of highly sensitive temperature sensing materials.